Moringa oleifera seeds as a flocculant in waste sludge treatment - Muyibi, Suleyman Aremu; Megat Mohd Noor, Megat Johari; Ong, Ding Tai; Kai, Khor Woon (Taylor and Francis Group, 2001)
In this study the results of a laboratory based investigation to determine the effectiveness of Moringa oleifera seeds as a flocculant for activated sludge treatment are presented. Waste sludge samples are activated sludge from Taman Dr. Tun. Ismail Activated Sludge Wastewater Treatment plant, Kuala Lumpur, Malaysia. Moringa oleifera seed was applied as dry powder (shelled blended), solution (shelled blended), and solution (shelled blended oil extracted). Results of vacuum filtration studies showed that residual sludge volume of up to 11%, 20% and 45% for shelled blended oil extracted, shelled blended, and control (no Moringa applied), respectively, was achievable. Sludge volume reduction of up to 67% was achievable using gravity settling for shelled blended solution and 48% for shelled blended oil extracted respectively compared to the control. The shelled blended category applied in powder form performed the same as the solution of shelled blended but performed better than the shelled blended oil extracted category in gravity settling. The specific cake resistance of sludge treated with shelled blended Moringa oleifera averaged 2.5 × 1012m/kg at 4000mg/l dosage. Vegetable oil from the shelled Moringa oleifera of up to 30% was obtained as a by product.